Arquitetura em museus brasileiros e a construção de utopias possíveis - João Pedro Pujoni Facury (2024)
The work investigates the contemporary forms of museum spaces and the link with the role played by architecture in these places. The museum is a complex institution, full of potential and undergoing intense transformation. In this field, architecture plays a fundamental role, since a large part of the institution's activities, its symbolic construction and the very understanding of the museum pass through its physical spaces. Based on conceptual and historiographical reviews, the work selected five reference institutions located in the Belo Horizonte Metropolitan Region as museum cases: the Pampulha Art Museum (MAP), the Museum of Arts and Crafts (MAO), the Luiz Estrela Common Space, the Viaduto das Artes and the Inhotim Institute. Their analysis, based on the institutional dimension - the symbolic field - and the physical dimension - the material field - contributed to the development of a regional museum scene, which portrays a contemporary museum panorama.